Seismic Design Method for Shield Tunnels in Ground Conditions Subject to Change in the Longitudinal Direction - TSUNO, Kiwamu; FUJITA, Kiichi; FUNAKOSHI, Koji (Quarterly Report of RTRI, 2023)
The authors of this paper investigated the effect of seismic motion on shield tunnels that are located in areas with varying ground conditions. This research revealed that the larger the inclination angle of a boundary between a basic layer and a soft layer becomes, the larger the sectional forces, such as axial force, bending moment and shear force become. In addition, the sectional force obtained by an equivalent stiffness beam model was found to be larger than that obtained by a beam-spring model. This research also confirmed that results using a beam-spring model when the inclination angle is 5.9 degrees satisfy verification requirements.